(untitled) (Ustozlar uchun, 2026)
This article examines the impact of air pollution on human health from environmental, medical, and public health perspectives. It analyzes the major sources of air pollution, including industrial emissions, motor vehicle exhaust, fossil fuel combustion, agricultural activities, and household pollutants, as well as their effects on human physiological systems. Particular attention is given to the health consequences of exposure to particulate matter (PM₂.₅ and PM₁₀), nitrogen dioxide (NO₂), sulfur dioxide (SO₂), ozone (O₃), carbon monoxide (CO), and volatile organic compounds (VOCs). The article discusses the relationship between air pollution and respiratory diseases, cardiovascular disorders, neurological conditions, cancer, adverse pregnancy outcomes, and premature mortality. Furthermore, it highlights international environmental standards, evidence-based preventive strategies, and the role of governments, healthcare professionals, and communities in reducing air pollution exposure and promoting public health. The study emphasizes the importance of sustainable environmental policies and clean air initiatives for improving global health outcomes.